2006
DOI: 10.1097/01.aids.0000226957.79847.d6
|View full text |Cite
|
Sign up to set email alerts
|

Generic fixed-dose combination antiretroviral treatment in resource-poor settings: multicentric observational cohort

Abstract: Positive outcomes for d4T/3TC/NVP are reported for up to 18 months in terms of efficacy and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
110
4
6

Year Published

2007
2007
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 20 publications
14
110
4
6
Order By: Relevance
“…Whereas several publications (Calmy et al, 2006;Spacek et al, 2006;Wester et al, 2005) and recent presentations from large cohorts in Uganda, Kenya and South Africa (Boulle et al, 2006;Forna et al, 2006;Kim et al, 2006) reported on toxicities such as neuropathy and lactic acidosis, lipoatrophy has not been stated as an important problem and this is in clear contrast to our data (van Griensven et al, 2006). There might be a number of possible reasons for this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Whereas several publications (Calmy et al, 2006;Spacek et al, 2006;Wester et al, 2005) and recent presentations from large cohorts in Uganda, Kenya and South Africa (Boulle et al, 2006;Forna et al, 2006;Kim et al, 2006) reported on toxicities such as neuropathy and lactic acidosis, lipoatrophy has not been stated as an important problem and this is in clear contrast to our data (van Griensven et al, 2006). There might be a number of possible reasons for this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…While other cohort data from the IDI [29] and other African centres [3,43-46] have reported excellent 12-month outcomes, this result is likely to have been affected by survival bias. Due to the cross-sectional nature of this study, our results may not account for early losses to follow up (from deaths, etc.)…”
Section: Discussionmentioning
confidence: 80%
“…8,10,11 The majority of patients in our cohort were treated with split adult FDC of 2 NRTIs and 1 NNRTI, confirming other findings that good outcomes can be achieved with this treatment strategy. 18,19 It should be noted, however, that this practice is a suboptimal interim strategy 13 pending prequalification of pediatric formulations of FDCs. The majority of the patients were in an advanced stage of HIV infection, similar to many settings where HIV/AIDS care for children has been commenced.…”
Section: Discussionmentioning
confidence: 99%